The Development of E-Learning Teaching Material Based on Edmodo on Basic Competencies of National Integration at Class X of Senior High School - Linda Solehana; Asrori Asrori; Andy Usman (JETL (Journal of Education, Teaching and Learning), 2019)
This research aims to determine (1) the design of E-learning teaching materials, (2) steps for using Edmodo-based learning materials (3) student learning behaviour in learning using Edmodo-based E-learning. The development model used is a procedural model adapted from the instructional design development model according to Dick & Carey while the development research model used is in accordance with Borg & Gall. The instrument used was in the form of a questionnaire instrument, interview guidelines and observation guidelines (observations). The data analysis used in this study is qualitative descriptive statistics. Noting the validation of experts and the results of trials in the field, it can be concluded that: (1) Edmodo-based E-learning teaching materials on Basic Competence (KD) of National Integration are appropriate to use for Class X (Grade 10th) SMA PPKn subjects; (2) Clarity of instructions for using E-learning teaching materials is considered good; (3) Changes in student learning behaviour are students who look very enthusiastic about learning by using E-learning teaching materials; (4) Edmodo-based E-learning materials are considered effective in achieving the learning objectives of the PPKn; (5) Edmodo-based E-learning teaching materials have a high time and place efficiency with regard to the limitations of available teaching materials; (6) Edmodo-based E-learning teaching material is a strategy for delivering messages that have high competitiveness. For research on the development of E-learning teaching materials based on Edmodo that will come to be more refined and better in order to support the smooth learning process.